2016
DOI: 10.1590/1983-40632016v4638707
|View full text |Cite
|
Sign up to set email alerts
|

Total alcoholic acidity and pH tests as quality parameters in stored soybean grains

Abstract: Despite the technology available to agriculture, qualitative and quantitative losses occurring during post-harvest are still not controlled, and stored grains may undergo changes in their composition, due to storage conditions. This study aimed at determining the sensitivity of the alcoholic acidity and pH tests in soybean (GB 874RR cultivar) grains with different quality standards obtained during storage. A completely randomized design, in a 3 x 6 x 5 (3 storage conditions x 6 storage times x 5 methods) facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…Thus, the maximum decomposition of the lipid components must occur between pH 5.0 to 5.5. Araújo et al (2016) found a high negative correlation (r=-0.781) between the acidity in the soybean and the ether extract content.…”
Section: Discussionmentioning
confidence: 88%
“…Thus, the maximum decomposition of the lipid components must occur between pH 5.0 to 5.5. Araújo et al (2016) found a high negative correlation (r=-0.781) between the acidity in the soybean and the ether extract content.…”
Section: Discussionmentioning
confidence: 88%
“…No ambiente desfavorável houve um crescimento acentuado nos teores desta variável a partir do segundo mês de armazenamento, que possivelmente pode ter ocorrido em função da deterioração dos grãos neste ambiente (Figura 7). O teor de acidez pode ter se elevado devido as porcentagem de grãos com incidência de fungos, como fermentados, ardidos e mofados, presentes neste ambiente (Araujo et al, 2016). Paraginski et al (2015), afirma que os ácidos graxos livres são consequência de atividade fúngica que está associada ao teor de água do grão da soja, onde acima de 14% de umidade ocorre crescimento fúngico e aumento considerável na produção de ácidos.…”
Section: Discussionunclassified
“…Desecado y triturado de la droga: 500 g de semillas de Glycine max fueron pesados y secados por el método gravimétrico de la estufa a 45°C hasta peso constante y después fue triturado en un mortero metálico (Remondetto et al, 2001;Araujo et al, 2016;Yuliani et al, 2018). Desengrasado y despigmentado de la droga: 20 g de la droga fueron triturados y mezclados con cantidad suficiente de arena lavada y tratada, se armó un cartucho de papel que fue introducido en la cámara del equipo Soxhlet, procediendo a extraer la grasa y los pigmentos con éter de petróleo, por 4 horas hasta agotar la grasa y los pigmentos (Rostagno et al, 2009;Yuliani et al, 2018).…”
Section: Extracción Y Purificación De Isoflavonas Totalesunclassified
“…Luego, se repitió todos los pasos descritos en la determinación de la capacidad antioxidante in vitro del extracto metanólico de isoflavonas totales (Tyug et al, 2010;Skowyra, 2014;Pisoschi et al, 2016). The average productivity of soybean in Brazil is 2,999 kg ha-1 (Araujo et al, 2016).…”
Section: Capacidad Antioxidante In Vitro Del Extracto Metanólico De I...unclassified